United but (un-)equal: Human capital, probability of divorce and the marriage contract - Helmuth Cremer; Pierre Pestieau; Kerstin Roeder (Institute for the Study of Labor (IZA), 2012)
This paper studies how the risk of divorce affects the human capital decisions of a young couple. We consider a setting where complete specialization (one of the spouses uses up all the education resources) is optimal with no divorce risk. Symmetry in education (both spouses receive an equal amount of education) then acts like an insurance device in case of divorce particularly when the institutions do not compensate for differences in earnings. But, at the same time symmetry in education is less efficient than the extreme specialization. This is the basic tradeoff underlying our analysis. We show that the symmetric allocation will become more attractive as the probability of divorce increases, if risk aversion is high and/or labor supply elasticity is low. However, it is only a second-best solution as the insurance protection is achieved at the expense of an efficiency loss. Efficiency can be restored through suitably designed marriage contracts because they can provide the appropriate insurance against divorce to a couple who opts for specialization. Finally, we study how the (economic) use of marriage is affected by the possibility of divorce.
Keywords: D13; J24; K36; 330; post-marital education; marriage contract; divorce; Ehe; Bildungsinvestition; Scheidung; Risiko; Familienökonomik; Vertrag; Theorie